Multi-Physics Model Development for Polonium Transport Behavior in a Lead-Cooled Fast Reactor - Lilin, Deng; Yuqing, Wang; Zian, Zhai; Bochen, Huang; Jiewei, Wu; Jianbo, He; Muyi, Ni (Frontiers in Energy Research, 2021)
210Po, a highly toxic element with strong volatility, is one of the main source term of Gen-IV Lead-cooled Fast Reactor (LFR). Therefore, the radiological safety issue caused by 210Po has become an important issue in LFR related research. In order to simulate the behavior of 210Po in LFR, this work developed a multi-physics model of LFR from the perspective of radioactive transport. Considering the effects of nuclides decays, cover gas leakages, containment ventilation and Po aerosol deposition, a comprehensive simulation was carried out to evaluate these effects on the 210Po concentration in detail. Preliminary results indicate that during normal operation, most of the 210Po in the LBE exists in the form of PbPo, and about 10-9 210Po could evaporate from the LBE into the cover gas, and then further leak into the containment. In addition, even if the leakage rate of 210Po in the cover gas into the containment is maintained at 5‰ per day, due to the deposition of 210Po itself, the 210Po contamination on the inner surface of the containment is still below the radioactivity concentration limits.